Aromatherapy Candle-Making with Used Cooking Oil: A CIPP Model-Based Community Training in Munding, Semarang - I'tishom Al Khoiry; Shofif Sobaruddin Akbar; Ika Menarianti; Dhea Rizky Amelia (NEAR: Jurnal Pengabdian kepada Masyarakat, 2025)
Used cooking oil is a common household waste that can cause pipe blockages and environmental pollution when improperly discarded into drainage systems. This community service program aimed to enhance literacy and practical skills in the safe reuse of used cooking oil through training on the production of aromatherapy candles. The activity involved members of the Family Welfare Empowerment Group (PKK) in Munding Urban Village, Bergas Subdistrict, Semarang Regency, who play key roles in promoting healthy and environmentally responsible household practices. The training combined environmental education, occupational safety awareness, and hands-on practice. The program was evaluated using the CIPP (Context, Input, Process, Product) framework to assess contextual relevance, resource adequacy, procedural adherence, and product quality. The results indicated 91 percent participation, 94 percent adequacy of inputs, 88 percent compliance with safe procedures, and an average product quality of 86 percent. These findings demonstrate that the program was feasible, safe, and easily replicable using household tools. Beyond technical outcomes, the initiative fostered circular economy awareness and strengthened community-based environmental empowerment through the PKK network, providing both social and environmental benefits at the household level.